Hybrid Corporeality and the Multiplicity of Human Death: A Post-Anthrocentric Perspective - Sokolovskiy, Sergei (Anthropologica, 2021)
Rapid development of cognitive and neurosciences undermined the Cartesian view on the human body as a bounded and autonomous entity. A plethora of publications on enhanced memory, external cognition, extended mind, embodied self, or distributed corporeality confirms the view that the human body and mind are not self-contained entities, producing the world as a prosthetic set of “extensions” or parts of hybrid wholes, which we interpret as cyborganic assemblages. However, in this abundance of documented entanglements of bodies and minds with their surrounding settings, of fusions of corporeality with inert matter, there is scarce, if any, reflection on the posthumous fate of these hybrids and on the multiple forms of their deterioration, that establish what the author provisionally describes as multiplicity of human death. The paper presents the analysis of various forms of human body and inanimate matter integration and their posthumous persistence or deterioration. The view on the human body as multiple provides corollary of its death as a multimodal, manifold set of events, distinguishing biological, lived, and social bodies and their heterochronous deaths. The heterochronicity of human death is illustrated with the description of private commemorative practices that form a geography, distinct from the usual public commemoration places.